PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI SEKRETARIAT DPRD KABUPATEN TUBAN - Yeni Mei Putri; Hadi Sunaryo; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThis research aims to know the influence of performance area,disciplinary performance, and performance motivation toward the performance ofDPRD secretariat official of Tuban Regency.This research includes of Explanatory Research. The research data ofperformance area, disciplinary performance, and performance motivation towardthe performance of DPRD secretariat official of Tuban Regency acquired formDPRD secretariat of Tuban Regency. The populations of this research are thewhole of DPRD secretariat official of Tuban Regency. The data collection usedquestionnaire and documentation. Then, the data analysis used instrument test,normatitas test, bifilar linear regression, classis assumption, and hypothesis test.Based on the finding of this research, it can be concluded that the variableof performance areapartially gives significant influence toward officialperformance, whereas disciplinary performance does not significantly influenceofficial performance, while performance of motivation significantlyinfluenetoward official performance.Keywords: performance area, disciplinary performance, performance motivation